COMPARISON OF CONVENTIONAL RADIATIOTHERAPY AND ACCELERATED HYPERFRACTIONATED RADIATIOTHERAPY IN CHEMORADIATION TREATMENT FOR SMALL CELL LUNG CANCER - I. A. Gulidov; A. G. Zolotkov; Yu. S. Mardynsky; I. N. Ivanova; L. V. Kursova; D. V. Gogolin; Yu. A. Ragulin (Сибирский онкологический журнал)
The 5-year treatment outcomes of 69 patients with stage IIA–IIIA locally advanced small cell lung cancer have been presented. Accelerated hyperfractionated radiotherapy was administered in the uneven daily dose fractionation (single dose of 1 + 1,5 Gy with a 5–6hour interval to a total dose of 60–70 Gy) depending on the health status and lung function. The complete response was achieved in 13 (42 %) patients, the median survival was 28 months and the 5-year survival rate was 26,2 %. Grade III lung and pericardium toxicities (according to RTOG toxicity scale) were observed in 3,2 % and 6,5 % of patients, respectively. No grade III–IV radiation-induced blood and esophageal damages were found.